Between Energy Neocolonialism and the Cold War: A Comparative Analysis of Oil Nationalism in Venezuela and Iran (1948-1979) - Cardozo-Uzcátegui, Alejandro (2025)
This study examines the visible elements and parallels in the nationalist petroleum endeavors of Venezuela and Iran, which are comparable in light of their respective contexts vis-à-vis the enterprises and interests of North Atlantic countries up to the establishment of the OPEC scenario. It represents a comparative journey beginning in the early twentieth century, highlighting critical junctures and long-term similarities in processes where causal factors—such as energy neocolonialism, nationalism, democratic revolutions, dictatorships, and monarchies—converge within the complex constellation of forces forged during the Cold War.